What Are Preadolescent Readers Doing Online? An Examination of Upper Elementary Students' Reading, Writing, and Communication in Digital Spaces. Issue 4 (1st April 2016) - Hutchison, Amy C.; Woodward, Lindsay; Colwell, Jamie
Abstract: The online reading, writing, and communication practices of students have been of significant interest to literacy researchers and teachers throughout the last several years, as insights into what students are currently doing in and outside of school can inform what they can be expected to know and be able to do in digital environments. Yet, little is known about the online activities, perceptions, preferences, and skills of preadolescent students. The present study reports the performance of 1, 262 fourth and fifth graders on the Survey of Internet Use and Online Reading. Results were analyzed to determine whether there are gender differences in preadolescent students' Internet activities, perceptions, preferences, and skills. Findings from descriptive and comparative analyses of students' responses indicate that (a) preadolescent students in this study are moderately skilled at online search, evaluation, and communication tasks, with females scoring significantly higher on digital tasks than males; (b) preadolescent students engage in many digital tasks more frequently in school than outside of school; (c) despite reporting a preference for using the Internet, preadolescent students believe that it is more difficult to use it than to read a book, and believe that they would learn more from a book than from the Internet; and (d) there is a significant gender difference in students' skills and confidence related to digital tasks, and students' perceptions of their own skills may not align with their achievement on digital skills–based tasks.